Quantifying Impairments in the Subacute Phase of Whiplash Associated Disorders—A Cross-Sectional Study - Harpa Ragnarsdóttir; Guðný Lilja Oddsdóttir; Magnús Kjartan Gíslason; Kristín Briem (Life)
Whiplash-Associated Disorders (WADs) often result from traffic accidents, leading to persistent symptoms, including neck pain, disability, dizziness, and central sensitization (CS). A key concern is cervical range of motion (cROM) impairment and sensorimotor dysfunction, which contribute to prolonged disability. This study assessed functional performance in individuals with subacute (>1, <3 months) WADs (n = 122) compared to healthy controls (n = 45). Clinical measures included cROM, movement control (Butterfly test), and position sense (Head–Neck Relocation Test, HNRT). Patient-reported outcomes included neck disability, pain intensity, central sensitization, and dizziness. Mixed and linear models evaluated group differences and the influence of demographic and symptom-related factors. WAD patients had significantly reduced cROM and impaired movement control (p < 0.001). Neck disability (p < 0.001) and pain intensity (p = 0.015) affected cROM within the WAD group. Interaction effects revealed greater amplitude accuracy (AA) impairments at greater difficulty levels (p = 0.043), while time on target (TOT) differences decreased (p < 0.001). Dizziness was associated with increased undershoot (p < 0.001), while pain negatively impacted both AA (p = 0.003) and TOT (p = 0.037). Position sense did not differentiate WAD patients from controls. Findings suggest task-dependent sensorimotor deficits, highlighting the need for multimodal assessment. Early CS screening may optimize rehabilitation and prevent chronic disability.